From Code to Culture: A Semiotic Analysis of Digital Resistance in Indonesian Open-Source Communities - rusnalasari, zulidyana d; Hidayah, Layli (Lakon : Jurnal Kajian Sastra dan Budaya, 2025)
This article builds on a study of the BlankOn Linux movement in Indonesia, examining how local open-source communities perform digital resistance through semiotic and ideological practices. Using Roland Barthes’ semiotic theory, Stuart Hall’s representation theory, and Antonio Gramsci’s concept of hegemony, the research analyzes community-produced artifacts, logos, naming conventions, website design, and documentation to uncover how they encode counter-hegemonic meanings. Data were collected through image analysis, discourse analysis of digital texts, and email interviews with community members. Findings show that BlankOn fuses local-nationalist values, such as the promotion of the Indonesian language and cultural identity, with global open-source principles like gift culture and collaborative production. This hybrid identity challenges the dominance of proprietary software ecosystems, positioning the movement as both a technological innovator and a cultural-political actor. The analysis reveals that resistance in BlankOn is enacted less through direct confrontation and more via symbolic strategies that naturalize alternative technological ideologies.